Recent dengue virus infection: epidemiological survey on risk factors associated with infection in a medium-sized city in Mato Grosso - Trettel, Ana Cláudia Pereira Terças; Ferreira, Dandára Thaís de Oliveira; Atanaka, Marina; Espinosa, Mariano Martinez; Faccini, Lavinia Schuler; Caldeira, Aline da Silva; Silva, Juliana Herrero da; Oliveira, Viviane Karolina Vivi; Paz, Rayana de Castro da; Nascimento, Vagner Ferreira do (São Paulo Medical Journal, 2022)
BACKGROUND: Dengue is considered to be the most important arbovirus worldwide, with important complications that increase its lethality. In Brazil, an endemic country, the disease reaches significant incidence levels, with occurrences of serious cases and high costs of hospitalizations for its treatment. OBJECTIVE: To analyze risk factors among individuals with recent histories of dengue infection in a medium-sized city in Mato Grosso. DESIGN AND SETTING: Descriptive cross-sectional study, of epidemiological-survey type, conducted among the urban population of a city located in mid-northern Mato Grosso. METHODS: A seroepidemiological survey using questionnaires and collection of biological material was conducted among 596 adults aged ≥ 18 years who had been selected through a cluster sampling process. Positive dengue cases were those with positive results from anti-dengue immunoassays (ELISA). Statistical analyses with descriptive and inferential techniques were used, with 95% confidence intervals and a 5% significance level. RESULTS: The seroepidemiological profile of the study participants was predominantly female, with ages between 18 and 39 years, self-declared non-white race/color, not more than eight years of education and not living with a companion. Among the sanitary factors analyzed, the following were risk factors for dengue virus infection: no running water at home; no water supply from the public piped network; no waste from drains or toilets sent to the sewage network; endemic disease combat agents visiting the home; and presence of mosquito breeding sites at home. CONCLUSION: Low schooling levels and previous dengue virus infection were associated with current dengue virus infection.